Evaluation of SnSe crystals fabricated by temperature gradient method with double tubes seal. Issue 7 (17th May 2018) - Tsujioka, Yusuke; Tahashi, Masahiro; Ichino, Yusuke; Tsuchiya, Yuji; Goto, Hideo; Yoshida, Yutaka
Abstract: Thermoelectric power generation can effectively utilize waste heat. ZT representing the performance of thermoelectric materials is required to have a value of 2 or more for the applications. SnSe with a high ZT of 2.6 has an anisotropy of thermoelectric properties due to the crystal structure. Since heat exists in various places, many SnSe single crystals are considered to be necessary. Here we attempted to grow single crystals of SnSe by a temperature gradient method as a simple technique. Also we prevented evaporation of SnSe with double tubes seal. We fabricated SnSe crystals at the cooling rates of 5, 10, and 50℃/h using MgO (100) single crystalline substrate as seed crystal. The SnSe crystal fabricated at a cooling rate of 50℃/h was shown to be polycrystal. On the other hand, the SnSe crystal fabricated at a slower cooling rate of 10℃/h was shown to be pseudo‐single crystal with stoichiometric composition. The temperature dependence of the electric conductivity and the Seebeck coefficient of the SnSe crystals was the same tendency as that of SnSe single crystal.